Peningkatan Kemampuan Motorik Kasar Anak Melalui Permainan Loncat Geometri - Afrella Dewita, Cindy; Marlina, Serli (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Children often struggle with low self-confidence, largely because they have difficulty performing physical or motor activities. Additionally, there are many children who display reluctance or lack of enthusiasm for engaging in tasks that require physical effort. This study aimed to assess the improvement in children's gross motor skills through geometric jumping games at Taman Kanak-Kanak Kasih Ibu Sijantang Koto. The research method used was Classroom Action Research (CAR). The participants of the study were children attending Taman Kanak-Kanak Kasih Ibu Sijantang Koto, with a class size of 10 students. The study was conducted over several cycles, each consisting of four key stages: planning, action implementation, observation, and reflection. The findings indicated that the children's gross motor skills showed significant improvement with the geometric jump game. Specifically, their ability to perform jumping movements with correct foot support increased from 20% to 80%. Their ability to maintain balance while jumping improved from 20% to 80%. Moreover, the children's participation in the geometric jump game increased from 10% to 70%, and their ability to accurately describe geometric shapes rose from 10% to 70%.